2016
DOI: 10.1039/c6em00344c
|View full text |Cite
|
Sign up to set email alerts
|

Metabolization and degradation kinetics of the urban-use pesticide fipronil by white rot fungus Trametes versicolor

Abstract: Fipronil is a recalcitrant phenylpyrazole-based pesticide used for flea/tick treatment and termite control that is distributed in urban aquatic environments via stormwater and contributes to stream toxicity. We discovered that fipronil is rapidly metabolized (t = 4.2 d) by the white rot fungus Trametes versicolor to fipronil sulfone and multiple previously unknown fipronil transformation products, lowering fipronil concentration by 96.5%. Using an LC-QTOF-MS untargeted metabolomics approach, we identified four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 64 publications
2
29
0
1
Order By: Relevance
“…Biofilter performance may be improved in various ways, such as alteration of the hydraulics of the system and creation of a submerged zone, 43,44 addition of plants or fungi with pollutant-removal capabilities, [45][46][47][48][49] or alteration of geomedia. Though certain types of engineered geomedia have proven effective for targeted contaminant removal (e.g., manganese-oxide, iron-oxide coated sands, 50,51 surfacemodified biochar, 52,53 and functionalized polymer clays 54 ), Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Biofilter performance may be improved in various ways, such as alteration of the hydraulics of the system and creation of a submerged zone, 43,44 addition of plants or fungi with pollutant-removal capabilities, [45][46][47][48][49] or alteration of geomedia. Though certain types of engineered geomedia have proven effective for targeted contaminant removal (e.g., manganese-oxide, iron-oxide coated sands, 50,51 surfacemodified biochar, 52,53 and functionalized polymer clays 54 ), Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The strain ECS-79 was identified as Trametes versicolor. There are several reports on the degradation potential of this species and together with P. chrysosporium, is one of the most frequently studied macromycete species regarding the degradation of xenobiotic compounds such as aromatic polycyclic hydrocarbons (anthracene and naphthalene) (Marco-Urrea et al 2010;Jelic et al 2012;Wolfand et al 2016;Kamei 2017). This paper represents the first study that analyses the breakdown of the herbicide paraquat by both of these strains.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, some fungi could associate extracellular oxidoreductases with intracellular enzymes such as the cytochrome P450 system (cyt450). In the effort to better characterize the degradation skills of T. versicolor, cyt450 inhibitors were used: fungal performances against clofibric acid and fipronil decreased (Marco-Urrea et al 2009;Wolfand et al 2016). Mori et al (2017) suggested that cyt450 of Phanerochaete sordida is involved in the first reduction of the clothianidin N-nitro group but the enzymes responsible of the further urea derivatives production are unknown.…”
Section: Bioremediation Of Oacs By Fungi In Aquatic Ecosystemmentioning
confidence: 99%